(untitled) (Global Journal of Science Frontier Research, 2013)
There are two fundamental reasons for treatment of wastewater viz., prevention of pollution and thereby protecting the environment, and protecting the public health by safe guarding water supplies and preventing the spread of water borne diseases. Proper design, construction together with good operation and maintenance are essential for waste water treatment plants, in order to produce effluents which are satisfying the safe disposal standards prescribed by the regulatory authorities. In the present study a comprehensive design developed for the units of Inlet chamber, Screen chamber, Grit Removal Unit, Equalization Tank, Clari-Floculator, Aeration Tank, Sand Gravity Filter, Sludge Drying Beds etc. as they are commonly used in the field of wastewater treatment. The plant will use as many sustainable and energy efficient concepts as possible, while still keeping construction and maintenance costs low. The overarching goal of the project is to prevent the contamination of the aquifer, while also minimizing the environmental impacts on the surrounding ecosystems.